Evaluating integrated development environments using the TOPSIS method and Schweizer-Sklar power aggregation operator: implications for university students’ psychological management - Lijun Ma; Fengyu Guo; Zeeshan Ali; Shi Yin (Discover Applied Sciences)
Abstract University students, particularly those in computer science and engineering, often face high levels of stress due to complex coding tasks and project deadlines. This manuscript applies circular bipolar complex fuzzy linguistic sets, incorporating positive and negative membership functions with radius functions, and linguistic variables to address uncertainty in decision-making, aiming to reduce cognitive load and stress. We design algebraic and Schweizer-Sklar operational laws for circular bipolar complex fuzzy linguistic numbers. Using these operations, we propose four power aggregation operators: the circular bipolar complex fuzzy linguistic Schweizer-Sklar power averaging operator, weighted averaging operator, geometric operator, and weighted geometric operator, and explore their properties. Furthermore, we develop a Technique for Order of Preference by Similarity to the Ideal Solution (TOPSIS) model tailored to circular bipolar complex fuzzy linguistic information, incorporating both positive and negative ideal solutions. This model supports university students in evaluating Integrated Development Environments (IDEs), which are essential tools for debugging, writing, and testing code. Our goal is to reduce students' cognitive load and stress while improving their programming experience. We also create a decision-making model based on circular bipolar complex fuzzy linguistic values to evaluate IDEs effectively. Finally, numerical examples are presented to compare the proposed ranking results with existing ones, demonstrating the effectiveness of these methods in optimizing IDE selection and supporting students' psychological well-being.